2022
DOI: 10.1002/ece3.8678
|View full text |Cite
|
Sign up to set email alerts
|

Diversity investigation by application of DNA barcoding: A case study of lepidopteran insects in Xinjiang wild fruit forests, China

Abstract: To investigate the species diversity of lepidopteran insects in Xinjiang wild fruit forests, establish insect community monitoring systems, and determine the local species pool, we test the applicability of DNA barcoding based on cytochrome c oxidase subunit I ( COI ) gene for accurate and rapid identification of insect species. From 2017 to 2019, a total of 212 samples with ambiguous morphological identification were selected for DNA barcoding analysis. Five seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Traditional morphological classification methods of insects remain relevant in taxonomy for describing the diversity of insects [23]. However, identifying species through this morphological method using a microscope proves challenging because it requires indepth knowledge [24,25] to differentiate closely related species [26]. The use of DNA-based methods in the identification of species has several advantages, such as the reproducibility of results [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional morphological classification methods of insects remain relevant in taxonomy for describing the diversity of insects [23]. However, identifying species through this morphological method using a microscope proves challenging because it requires indepth knowledge [24,25] to differentiate closely related species [26]. The use of DNA-based methods in the identification of species has several advantages, such as the reproducibility of results [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have indicated that as most species move to new habitats, their population genetic structure and molecular diversity shift, as noticed in a few exotic species (Rubinoff et al, 2011;Xia et al,2020;Buj et al, 2022). In this connection, due to its variability, tight maternal genetic inheritance, lack of genetic recombination and suitability for analyzing population genetic makeup and seeking the origin of organism differences, mitochondrial DNA is well suited for these purposes (Shashank et al, 2014;Sarma et al, 2016;Zhan et al,2022). Furthermore, mtDNA is a reliable indicator of differences between and within populations (Margam et al, 2011;Xu et al, 2022).…”
mentioning
confidence: 99%